2017
DOI: 10.1007/s11255-017-1747-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise during hemodialysis prevents the decrease in natural killer cells in patients with chronic kidney disease: a pilot study

Abstract: This study suggests the potential role of intradialytic exercise to prevent the decrease in peripheral frequency of NK cell subsets during HD therapy. Moreover, moderate intensity intradialytic exercise did not exacerbate the systemic inflammation or induce muscle damage during HD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Zhang et al found that NK cells can directly damage renal tubular epithelial cells in vitro and that perforin is also involved in their cytotoxic acquisition and deeply involved in brosis during their evolution [35][36]. Similarly, the accumulation of NK cells in renal tubules leads to irreversible renal brosis [37][38][39]. This is consistent with our data suggesting a correlation between renal brosis and increased perforin and IFN-γ.…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al found that NK cells can directly damage renal tubular epithelial cells in vitro and that perforin is also involved in their cytotoxic acquisition and deeply involved in brosis during their evolution [35][36]. Similarly, the accumulation of NK cells in renal tubules leads to irreversible renal brosis [37][38][39]. This is consistent with our data suggesting a correlation between renal brosis and increased perforin and IFN-γ.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, Fuhro et al 24 reported that intradialytic exercise does not have the additional effect of removing systemic solutes (i.e., urea and creatinine) nor does it alter C-reactive protein levels, corroborating our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Previously published data reported the peripheral frequency of Natural Killer cells and cytokine levels in response to intradialytic exercise. 7,9 The non-inclusion criteria included patients with severe heart disease, uncontrolled arterial hypertension, thrombosis, ischemic cardiopathy, amputation, excessive pallor, severe dyspnea, femoral fistula, precordial pain, orthopedic or neurological compromising, and cognitive impairment. Additionally, eight healthy elderly (age between 60 and 80 years) individuals with no apparent diseases (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…6 The effects of intradialytic exercise also impact inflammatory cytokines and the modulation of the peripheral proportions of several immune cells. 68 Here, we aimed to evaluate the effects of a single session of intradialytic moderate-intensity exercise on CCR5+ monocytes and lymphocytes of elderly individuals with CKD.…”
Section: Introductionmentioning
confidence: 99%